Innovation by Negotiation: Case Studies Among British White-Collar Unions - Smith, Anthony (Relations industrielles / Industrial Relations, 1990)
On the basis of a series of case studies, this paper suggests that the influence of white-collar local unionism is often considerable. A key factor suggested here is the nature of existing relationships between management and union. Where cooperative industrial relations have prevailed, management is often willing to make concessions in order to sustain consensus.